Organizational Justice and its Role in Strengthening Social Cohesion: A Field Study of Employees at Erbil Polytechnic University - Mohammed, Asst. Prof. Dr. Aso Wali Mohammed (Sulaimani Journal for Humanities, 2025)
This study aims to identify the understanding of employees at Erbil Polytechnic University in Erbil city regarding the dimensions of organizational justice, and to assess the level of social cohesion among the employees at Erbil Polytechnic University in Erbil city. To achieve this, the study was conducted on a random sample of 200 employees at Erbil Polytechnic University. The researcher used a questionnaire as a tool to collect raw data from the study sample, utilizing the Organizational Justice Scale and Social Cohesion Scale, along with statistical methods to process the raw data. The study results indicated the role of organizational justice in strengthening social cohesion in the organization in question. The statistical analysis also revealed a significant relationship between organizational justice and social cohesion in the researched organization, suggesting that sound organizational justice positively impacts achieving social cohesion among individuals working in the organization. Additionally, the statistical analysis showed the influence of organizational justice on the dimensions of social cohesion. Based on the findings, the researcher recommended adopting a system to enhance organizational justice in educational sectors, utilizing it to increase organizational commitment among employees within those sectors. Furthermore, it was advised to develop policies and strategies regarding how supervisors interact with employees based on mutual interest and respect.
Keywords: Organizational Justice; Distributive Justice; Procedural Justice; Interactional Justice; Social Cohesion